On time fractional Cahn-Allen equation - Cui, Runqing (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In [1], Ozkan Guner et al. obtained some exact solutions of the time fractional Cahn-Allen equation. By using the method proposed in [10], we have tested these solutions and have found that they are not the solutions of this equation.